2019
DOI: 10.3892/mmr.2019.10563
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated microRNA‑671‑3p promotes tumor progression by suppressing forkhead box P2 expression in non‑small‑cell lung cancer

Abstract: In the present study, the expression of microRNA (miR)-671-3p in non-small-cell lung cancer (NSCLC) was detected via reverse transcription-quantitative polymerase chain reaction analysis, and its role in cell proliferation, apoptosis, migration and invasion was investigated via Cell Counting Kit-8, colony formation, flow cytometry, Transwell and scratch assays, respectively. It was observed that the expression of miR-671-3p was upregulated in NSCLC tissues and cell lines (A549 and H1975). Treatment with miR-67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…30 In NSCLC, FOXP2 expression was also considered negatively correlated with the progression of NSCLC. 26 Consistent with previous studies, we also found that FOXP2 expression was decreased in Figure 6 Effects of FOXP2 silencing on the progression of NSCLC cells. A549 and NCI-H23 cells were co-transfected with hsa_circ_0043265 overexpression plasmid and si-FOXP2 or their negative controls (circ-NC and scramble).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…30 In NSCLC, FOXP2 expression was also considered negatively correlated with the progression of NSCLC. 26 Consistent with previous studies, we also found that FOXP2 expression was decreased in Figure 6 Effects of FOXP2 silencing on the progression of NSCLC cells. A549 and NCI-H23 cells were co-transfected with hsa_circ_0043265 overexpression plasmid and si-FOXP2 or their negative controls (circ-NC and scramble).…”
Section: Discussionsupporting
confidence: 91%
“…25 Li et al determined that FOXP2 was downregulated in NSCLC and could act as a target of miR-671-3p to participate in the regulation of miR-671-3p on the progression of NSCLC. 26 Therefore, FOXP2 might act as an important negative regulator of NSCLC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient group comparison at diagnosis based on their overall survival showed that miR-328, miR-671-3p, miR-636 and miR-363 are upregulated in relapsed patients. These miRs are described in the literature as promising prognostic biomarkers in AML or other malignant diseases [ 21 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Interestingly, all the patients involved in this comparison were not grafted, which suggests that these four miRs could constitute a signature to guide the choice of the best treatment strategy, especially the utility of grafting patients at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a key regulator of m6A methylation by promoting m6A methylation of mRNAs at the 3'-UTR. ZC3H13 has been shown to serve as a tumor suppressor in colorectal cancer (Zhu et al, 2019). Zhu D,Zhou J,Zhao J,Jiang G,Zhang X,Zhang Y,Dong M. ZC3H13 suppresses colorectal cancer proliferation and invasion via inactivating Ras-ERK signaling.…”
Section: Zinc Finger Ccch Domain-containing Protein 13 Encoded By Thmentioning
confidence: 99%
“…Numerous recent studies indicate a tumor suppressor like role for FOXP2 (Campbell et al, 2010;Cuiffo et al, 2014;Yan et al, 2015;Diao et al, 2018;Song et al, 2017;Li et al, 2019), others present evidence for an oncogene-like role of the protein (Campbell et al, 2010;Zhong et al, 2017;Wu et al, 2018;.…”
Section: Forkhead Box Protein P2 Encoded By Foxp2 Genementioning
confidence: 99%